Signalment and Blood Types in Cats Being Evaluated as Blood Donors at Two Italian University Blood Banks - Eva Spada; Arianna Miglio; Daniela Proverbio; Maria Teresa Antognoni; Giada Bagnagatti De Giorgi; Elisabetta Ferro; Vittorio Mangili (Veterinary Medicine International)
Data from potential feline blood donors presented at two university blood banks in Italy were recorded. Blood typing was performed using an immunochromatographic method. Over the three years of the study 357 cats representing 15 breeds, 45.3% female and 54.7% male, with a mean age of 3.8 years were evaluated. Of these 90.5% were blood type A, 5.6% type B, and 3.9% type AB. The majority of the cats (54.6%) were European DSH (92.3% were type A, 5.1% type B, and 2.6% type AB), and 21% were Maine Coon (MCO) cats (100% blood type A). The estimated frequencies of transfusion reactions following an unmatched transfusion between DSH (donors and recipients), MCO (donor and recipients), DSH donors and MCO recipients, and MCO donors and DSH recipients were 4.8%, 0%, 0%, and 5.1% for major reactions and 7.2%, 0%, 7.7%, and 0% for minor transfusions reactions, respectively. In a population of blood donors that includes DSH and MCO the risk of transfusion reaction is between 5% and 8% if typing is not performed on donor and recipient blood. Blood typing should therefore be performed before transfusion to remove the risk of transfusion reactions due to blood type incompatibilities.